The Andean zinc rush: Green extractivism and climate vulnerabilities in the Peruvian highland waterscapes - Anna Heikkinen (Journal of Political Ecology, 2024)
Zinc is a green mineral that is increasingly required for manufacturing low-carbon technology. This demand has been promoted mainly by the Global North-led green policies to mitigate the impacts of climate change. However, simultaneously expanding zinc mining risks further entrenching climate threats in fragile socio-ecological environments such as the Peruvian highlands. This article analyses the linkages between the accelerated green extractivism of zinc and its associated climate-related vulnerabilities in the Cunas watershed in the Central highlands of Peru. The study draws on ethnographic-oriented fieldwork in the area in 2019, and 2022 and a review of policy documents on climate mitigation and zinc mining in Peru. The analysis particularly focuses on the recently reopened Azulcocha zinc mine and its intertwined socio-ecological effects on the local waterscapes amid climate change. The analysis draws the theoretical approaches of the political ecology of green extractivism and vulnerability to disentangle the multi-scalar power dynamics embedded in the global low-carbon transition and green extractivism and how these shape climate-related vulnerabilities. The study shows that with the impacts of climate change, accelerated extractivism risks (re)producing multiple vulnerabilities in the Andean highland communities. The findings highlight the urgent need to rethink the global climate proposals in such a way that they do not deepen climate damage in the already marginalized waterscapes in the Andes and elsewhere in the Global South.